(untitled) (New Jersey, 2008)
wenty-First Century Psychotherapies offers a remarkably comprehensive, up-to-date, and scholarly examination of the dominant approaches to therapy. Written by leading and articulate experts in each intervention model, this book draws together the most forward-thinking perspectives in individual, group, and couples/family therapy. This will be a treasured reference to novice and experienced clinicians alike, and I expect it to be a much-consulted companion to professionals for many years to come.
Keywords: Psychotherapy,Tâm lý trị liệu